Lesion-aware attention network for diabetic nephropathy diagnosis with optical coherence tomography images - Liu, Yuliang; Zhang, Fenghang; Gao, Xizhan; Liu, Tingting; Dong, Jiwen (Frontiers in Medicine, 2023)
Purpose For early screening of diabetic nephropathy patients, we propose a deep learning algorithm to screen high-risk patients with diabetic nephropathy from retinal images of diabetic patients. Methods We propose the use of attentional mechanisms to improve the model’s focus on lesion-prone regions of retinal OCT images. First, the data is trained using the base network and the Grad-CAM algorithm locates image regions that have a large impact on the model output and generates a rough mask localization map. The mask is used as a auxiliary region to realize the auxiliary attention module. We then inserted the region-guided attention module into the baseline model and trained the CNN model to guide the model to better focus on relevant lesion features. The proposed model improves the recognition of the lesion region. Results To evaluate the lesion-aware attention network, we trained and tested it using OCT volumetric data collected from 66 patients with diabetic retinal microangiopathy (89 eyes, male = 43, female = 23). There were 45 patients (60 eyes, male=27, female = 18) in DR group and 21 patients (29 eyes, male = 16, female = 5) in DN group. Our proposed model performs even better in disease classification, specifically, the accuracy of the proposed model was 91.68%, the sensitivity was 89.99%, and the specificity was 92.18%. Conclusion The proposed lesion-aware attention model can provide reliable screening of high-risk patients with diabetic nephropathy.